INDIRECT TRANSLATION OF EMOTIONAL AND PSYCHOLOGICAL EXPRESSIONS IN REMARQUE’S DER WEG ZURÜCK: A GERMAN–RUSSIAN–UZBEK COMPARATIVE ANALYSIS (Global Conference on Multidisciplinary Research and Innovation, 2026)
This study investigates the indirect translation of emotional and psychological expressions in Erich Maria Remarque’s novel Der Weg zurück (1928) through a comparative analysis of the original German text and its Russian and Uzbek versions. Adopting a tri-lingual corpus approach, we identify how metaphors, similes, and other figurative devices conveying trauma and sentiment are rendered across languages, with the Uzbek translation mediated via Russian. Drawing on Nida’s equivalence theory, Nord’s functionalism (Skopos theory), Komissarov’s categorization of equivalence, and other translation studies frameworks, we analyze shifts, losses, and strategies evident in the target texts. The Introduction outlines the novel’s context and the theoretical backdrop. The Methods detail the comparative textual analysis of selected passages exemplifying emotional nuance. In the Results, we present cases of preserved imagery (e.g. similes of restlessness) alongside notable shifts (e.g. metaphors of war trauma and vulgar insults toned down or altered), with deep linguistic and stylistic analysis of metaphor, symbolism, and figurative expression. The Discussion interprets these findings: we find that dynamic equivalence often guided translators to prioritize the effect on readers, sometimes at the cost of source-text stylistic richness, especially under the constraints of indirect translation. While the Russian and Uzbek translations succeed in communicating core emotions and psychological states to their audiences, they also illustrate the strengths (accessibility, cultural resonance) and limitations (semantic and tonal loss) inherent in indirect translation. The article concludes with reflections on maintaining emotional subtleties in translation and the importance of translator “loyalty” to both source text and target audience.
Keywords: Indirect translation; emotional expression; Remarque; Der Weg zurück; German–Russian–Uzbek; dynamic equivalence; Skopos theory; metaphor translation; translation shifts; war literature.